Impact of Canadian human immunodeficiency virus non-disclosure case law on experiences of violence from sexual partners among women living with human immunodeficiency virus in Canada: Implications for sexual rights. (February 2022) - Patterson, Sophie; Nicholson, Valerie; Gormley, Rebecca; Carter, Allison; Logie, Carmen H; Closson, Kalysha; Ding, Erin; Trigg, Jason; Li, Jenny; Hogg, Robert; de Pokomandy, Alexandra; Loutfy, Mona; et al.
Objectives: People living with human immunodeficiency virus in Canada can face criminal charges for human immunodeficiency virus non-disclosure before sex, unless a condom is used and their viral load is <1500 copies/mL. We measured the reported impact of human immunodeficiency virus non-disclosure case law on violence from sexual partners among women living with human immunodeficiency virus in Canada. Methods: We used cross-sectional survey data from wave 3 participant visits (2017–2018) within Canadian HIV Women's Sexual and Reproductive Health Cohort Study; a longitudinal, community-based cohort of women living with human immunodeficiency virus in British Columbia, Ontario and Quebec. Our primary outcome was derived from response to the statement: '[HIV non-disclosure case law has] increased my experiences of verbal/physical/sexual violence from sexual partners'. Participants responding 'strongly agree/agree' were deemed to have experienced increased violence due to the law. Participants responding 'not applicable' (i.e. those without sexual partners) were excluded. Multivariate logistic regression identified factors independently associated with increased violence from sexual partners due to human immunodeficiency virus non-disclosure case law. Results: We included 619/937 wave 3 participants. Median age was 46 (interquartile range: 39–53) and 86% had experienced verbal/physical/sexual violence in adulthood. Due to concerns about human immunodeficiency virus non-disclosure case law, 37% had chosen not to have sex with a new partner, and 20% had disclosed their human immunodeficiency virus status to sexual partners before a witness. A total of 21% self-reported that human immunodeficiency virus non-disclosure case law had increased their experiences of verbal/physical/sexual violence from sexual partners. In adjusted analyses, women reporting non-White ethnicity (Indigenous; African/Caribbean/Black; Other), unstable housing and high human immunodeficiency virus–related stigma had significantly higher odds of reporting increased violence from sexual partners due to human immunodeficiency virus non-disclosure case law. Conclusion: Findings bolster concerns that human immunodeficiency virus criminalization is a structural driver of intimate partner violence, compromising sexual rights of women living with human immunodeficiency virus. Human immunodeficiency virus non-disclosure case law intersects with other oppressions to regulate women's sexual lives.